OPTIMALISASI PARIWISATA KAWASAN SUKUH DAN CETO KABUPATEN KARANGANYAR DENGAN MENGGALI POTENSI SENI TRADISI - Santosa -; Muh. Arif Jati Purnomo; Joko Budiwiyanto; Sriharta - (Pascasarjana Institut Seni Indonesia Surakarta, 2011)
The article is the result of the research entitled â€œThe optimalization of tourism in Sukuh and Ceto areas, Kabupaten Karanganyar by increasing the potency of traditional art as a means of creative economic developmentâ€. The research aimed at making a model for developing an integrated tourism in Sukuh and Ceto areas which could be empowered as a an effort at increasing public economy and at strengthening local culture. A two-year research was carried out to attain the goal. The results of the first stage research are as follows: many kinds of art have been identified completely and comprehensively; a plan of developing art for tourism which can have an effect on economic development of the local society has been known; the model of art created is based on the approach of art for tourism with the following characteristics: an imitation of the original, compressedor short, the primary values are put aside, full of variation, attractive, and low in price. The conception of art for tourism is developed in accordance with the condition of the local society, culture, and the environment in order to create a specific art for tourism.Â The conception of art for tourism has the following characteristics. First, the art for tourism has a specific characteristic. Second, the art is specially designed considering the character of the area. Third, the art should have a contextual feature, meaning it is created by considering the natural elements, belief, customs, and local wisdom and it should not destroy the nature. Fourth, the art should pay attention to visual elements. Key words: traditional art, creative economy, art for tourism, model formulation.